Pirfenidone attenuates cardiac hypertrophy against isoproterenol by inhibiting activation of the janus tyrosine kinase-2/signal transducer and activator of transcription 3 (JAK-2/STAT3) signaling pathway. Issue 5 (2nd May 2022) - Chen, Zhenhuan; Zhou, Haiwen; Huang, Xiantao; Wang, Shaoyun; Ouyang, Xiaochao; Wang, Yunxia; Cao, Qianqiang; Yang, Liu; Tao, Yu; Lai, Hengli
ABSTRACT: Cardiovascular risk factors have attracted increasing attention in recent years with the acceleration of population aging, amongst which cardiac hypertrophy is the initiating link to heart failure. Pirfenidone is a promising agent for the treatment of idiopathic pulmonary fibrosis and has recently proven to exert inhibitory effects on the inflammatory response. This study proposes to explore the potential pharmacological action of Pirfenidone in treating cardiac hypertrophy in a rodent model. Four groups of mice were used in the present study: the control, ISO (5 mg/kg/day) for 7 days, Pirfenidone (200 mg/kg/day) for 14 days, and Spironolactone (SPI) (200 mg/kg/day) for 14 days groups. Increased heart weight index, left ventricle (LV) weight index, LV wall thickness, declined LV volume, and elevated serum levels of CK-MB, AST, and LDH were observed in ISO-challenged mice, all of which were dramatically reversed by the administration of Pirfenidone or SPI. Furthermore, an elevated cross-sectional area of cardiomyocytes in the wheat germ agglutinin (WGA) staining of heart cross-sections, upregulated atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), β Myosin Heavy Chain (β-MHC), and excessively released tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) in cardiac tissues were observed in the ISO group but greatly alleviated by Pirfenidone or SPI. Lastly, the promoted expression levels of p-JAK-2/JAK-2 and p-STAT3/STAT-3 in the cardiac tissues of ISO-challenged mice were significantly repressed by Pirfenidone or SPI. Collectively, our data reveals a therapeutic property of Pirfenidone on ISO-induced cardiac hypertrophy in mice.   Graphical abstract: uf0001